2016
DOI: 10.1080/02640414.2016.1255771
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Australian school-level rugby union

Abstract: There is a high incidence of injuries in rugby union due to the physical nature of the game. In youth rugby union, there are large variations in injury rates reported. Our study investigated the rates of injuries in school-level rugby union players in Australia using the consensus statement for rugby union injuries. Injury surveillance was conducted on 480 rugby players from 1 school in Queensland, Australia. Injury data were collected using paper-based injury recording forms during the 8-week rugby season usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…103 117 For example, Seminati et al reported a 13% higher impact force from the dominant shoulder. 132 Players seem to have poorer shoulder positional sense of their non-dominant shoulder while tackling 133 and adopt a more passive biomechanical strategy to generate the drive needed to stop a ball carrier. 132 As such, tackles on the dominant shoulder produce higher impact forces on contact, whereas the non-dominant shoulder produces force over longer durations.…”
Section: Injury Risk Factors and Performance Determinantsmentioning
confidence: 99%
See 3 more Smart Citations
“…103 117 For example, Seminati et al reported a 13% higher impact force from the dominant shoulder. 132 Players seem to have poorer shoulder positional sense of their non-dominant shoulder while tackling 133 and adopt a more passive biomechanical strategy to generate the drive needed to stop a ball carrier. 132 As such, tackles on the dominant shoulder produce higher impact forces on contact, whereas the non-dominant shoulder produces force over longer durations.…”
Section: Injury Risk Factors and Performance Determinantsmentioning
confidence: 99%
“…132 Players seem to have poorer shoulder positional sense of their non-dominant shoulder while tackling 133 and adopt a more passive biomechanical strategy to generate the drive needed to stop a ball carrier. 132 As such, tackles on the dominant shoulder produce higher impact forces on contact, whereas the non-dominant shoulder produces force over longer durations. 132 In addition, tackles on the non-dominant shoulder were characterised by less control of head movement, which had a more flexed and laterally bent position compared with tackles on the dominant shoulder.…”
Section: Injury Risk Factors and Performance Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rugby union (rugby) is a popular sport among schoolboys worldwide [1–3]. Today, schoolboy rugby players are playing more competitive matches and have better physical attributes than before [46].…”
Section: Introductionmentioning
confidence: 99%